Effective Atomic Number and Electron Density Determination of Some Amino Acids by Using Scattering Intensity Ratio of 59.54 keV Gamma Rays - Turşucu, Ahmet (Erzincan University Journal of Science and Technology, 2018)
In this study the specific atomic arguments have been determined for F-Glycine (C2H5O2N), Alenine (L, D) (C3H7O2N), Leucine (L, D) (C6H13O2N), L-Proline (C5H9O2N) amino acids. The calculation procedure of the experimental values of atomic parameters was carried out by using scattering intensity ratios of γ-rays. These γ-rays were obtained from 5 Ci 241Am annular radioactive source. In traditional studies, these arguments were determined by transmission technique. The scattered γ-rays were counted by using an HPGe semiconductor detector. Our detecting system was connected to a separate amplifier and an Accuspec card. Theoretical values of related atomic parameters for amino acid targets were calculated and cross checked with our experiential values. Our deliberated values are in good concordance with theoretical calculations.
Keywords: Amino Acids; Electron Density; Effective Atomic Number; Rayleigh to Compton Scattering Intensity Ratios